Inspirational Influence of Nature in Architectural Design – A Review on the Scope of Application in Nigeria Housing Policy - Tambe, E B; Essaghah, A E A; Ikegbunam, F I; Mbuka-Nwosu, I E; Okafor, N M; Ekpe, I N (Journal of Sustainability and Environmental Management, 2023)
The growing need for housing and infrastructural development is depleting and transforming green spaces to built environment. This transformation is altering the functioning of the natural processes that sustain life. However, conservation strategies through the science of biomimetic architecture show how nature offers the best ideas for regenerative infrastructural designs that humans can incorporate in planning. These natural forms of life provide insight on how designing housing and public infrastructures can promote efficiency in energy savings, waste management, nutrient provision, water management, adaptation to local condition, accommodating ecological hazards, sustaining the wellbeing of the occupants and reducing the frequency of visiting the natural capital. In Nigeria, housing policy programmes have primarily been focusing on ensuring affordable and available housing for all Nigerians. However, while the policy is being challenged in achieving its primary objective, it lacks biomimetic design in its elements, and ecological hazards (floods and erosion) are degrading/or destroying existing infrastructures in some Nigerian communities. Consequently, there is a need to integrate biomimetic designs in Nigeria housing policy and programme so as to capture the philosophy that a house is not only limited in providing shelter for humans, but also how the design of the house integrates into the natural functioning of the environment in resource provision, energy savings and environmental sustenance. The application of this approach can be achieved through the inclusion of biomimetic design incentives in building permit approval process to manage externalities associated with the infrastructure, while also taking into cognisance the housing needs of the poor, and the huge infrastructural investments of high income earners and the public. This approach will reshape consumption behaviour; develops a built environment that integrates and functions without resistance with its local condition in resource provision, waste management for its occupants, and enhance sustainability of resources base.